Skin tags and acanthosis nigricans in patients with hepatitis C infection in relation to insulin resistance and insulin like growth factor-1 levels - Omar Soliman El Safoury; Olfat G Shaker; May Mohsen Fawzy (Wolters Kluwer Medknow Publications, 2012)
Background: Skin tags (ST) are papillomas commonly found in the neck, axillae of middle-aged and elderly people Aim: Insulin and insulin-like growth factor (IGF-1) levels are affected by hepatitis C virus (HCV) infection and both of them may be implicated in the etiopathogenesis of ST and acanthosis nigricans (AN) through their proliferative and differentiating properties. So, the aim of this work was to evaluate the impact of HCV infection on ST and AN through the estimation of insulin resistance and IGF-1. Materials and Methods: Participants were arranged into four groups: (ST +ve / HCV +ve) 23 subjects, (ST+ / HCV -ve) 19 subjects, (HCV -ve / ST-ve) 20 subjects and (ST-ve /HCV +ve) 22 subjects. Age, ST size, color, number, AN, fasting glucose, fasting insulin, insulin resistance, IGF-1, HCV-antibodies (Ab) were recorded. Results: The mean number of ST in Group 1 was half the number of ST in Group 2 (11.0±9.3 / 22.3±14.0) (P=0.005). The difference in insulin resistance between the same groups was non-significant (13.1±10.6 / 9.0±5.5) (P=0.441) while the difference in IGF-1 was statistically significant (218.6±46.2 /285.4±32.8) (P=0.002). The multivariate logistic regression for the variables revealed that insulin resistance is the only factor affecting the occurrence of ST (OR=1.096, P=0.023). Multivariate regression analysis for the variables showed that HCV was borderline but not a significant factor affecting the number of ST (Beta=-0.409, P=0.053). The number of patients with AN was doubled in Group 2 in comparison to Group 1 but this was non significant 3(13%) / 6(32%) (P=0.2800). Conclusion: HCV is associated with a significant decrease in the ST number and in the serum level of IGF-1 together with an obvious decrease in the occurrence of AN. Our results may point to the entrant effect of insulin resistance and IGF-1 in ST and AN development. The current study suggests the evaluation of IGF-1-lowering agents in the control of ST and AN especially in the females with polycystic ovary and in the prevention of the recurrence of ST after surgical removal.